Persepsi Mahasiswa Terhadap Pembelajaran English Grammar Pada Mata Kuliah Bahasa Inggris - Siti Amalia Rachmawati; Achmad Zainul Mustofa Al Amin Al Amin (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
This study focuses on knowing students' perceptions of learning English grammar in English courses; this study also discusses students' perceptions of the level of understanding and ease of learning English grammar in English courses. This study uses a qualitative descriptive method to describe in detail the characteristics and phenomena to be analyzed. The technique used to collect data is through questionnaires. Questionnaires were used to obtain data on students' opinions on students' mastery of grammar and to find out students' difficulties in learning grammar. Questionnaires are distributed in online form via google form. In this study, the researcher took samples from 8 students of STIT Raden Wijaya in the grade of second semester who took English courseand given questions related to grammar and the problem being studied. Based on the research of the questions above, it can be seen that the majority of students answered agree that English is a science related to English that grammar is considered the most important because it serves as the basis for more advanced language learning. In addition, students who previously did not understand grammar felt that they began to understand and like grammar learning on campus because of the treatment given during the learning process, so learning grammar was very enjoyable. The students considered that grammar was important and some thought that grammar was beneficial for understanding English, but there were those who answered that it was beneficial for learning grammar, but grammar is a success factor for students in learning English